Game on! Tips, cheats & secrets : Adventure games - Walker-Emig, Paul; White, John; Ashby, Stephen (New York : Scholastic, Inc., 2017)
Adventure is everywhere in gaming, from exploring huge new worlds to playing a part in epic storylines. This book is packed with all the greatest adventure titles, with tips, tricks, and advice to help you finish you gaming quests.
27 reasons Zelda: Breath of the Wild will be amazing --Top 10 mobile adventures --Top 8 adventure stories -- Top 10 adventure classics --Top 8 exploration adventures -- Gamer challenge -- Retro revival: adventure -- Achievements & trophies! -- End game: Journey -- No Man's Sky -- Sea of Thieves -- The Legend of Zelda: Breath of the Wild -- King's Quest -- Paper Mario: Color Splash -- Recore -- Grow Up -- Lego Star Wars: The Force Awakens -- Spider Man -- Skylanders: Imaginators -- The Last Guardian --Which adventure game is right for you?
3-6
Keywords: Video games -- Handbooks, manuals, etc